Household Water Quality Testing and Information: Identifying Impacts on Health Outcomes and Sanitationand Hygiene-Related Risk-Mitigating Behaviors - Okyere, C.Y.; Pangaribowo, E.H.; Gerber, N. (Evaluation Review, 2019)
Background: In 2014, a group of 512 households in multipurpose water systems and also relying on unimproved water, sanitation, and hygiene practices in the Greater Accra region of Ghana were randomly selected to participate in water quality self-testing and also receipt of information in the form of handouts on how to improve water quality. Objectives and Research Design: Using a cluster-randomized controlled design, we study the health, sanitation, and hygiene behavior impacts of the household water quality testing and information experiment. Subjects: The study has three arms: (1) adult household members, (2) schoolgoing children, and (3) control group. Measures: The study measures the effects on handwashing with soap, cleanliness of households, and prevalence of diarrhea and self-reported fever. We also address impacts on child health and nutrition outcomes, particularly diarrhea and anthropometric outcomes. Results: We show that there is high household willingness to participate in this intervention on water quality self-testing. About 7 months after households took part in the intervention, the study finds little impacts on health outcomes and on sanitation- and hygiene-related risk-mitigating behaviors, regardless of the intervention group, either schoolchildren or adult household members. Impacts (direction and extent) are rather homogeneous for most of the outcomes across treatment groups. Conclusions: The study discusses the implications of the findings and also offers several explanations for the lack of transmission of impacts from the household water quality testing and information intervention on health outcomes and on sanitation and hygiene behaviors.
Research Article
Keywords: behavioral health care and policy; content area; economic evaluation; design and evaluation of programs and policies; methodology (if appropriate); program design and development; program implementation